Hubungan Status Refraksi Miopia terhadap Prestasi, Kejadian Mata Kering, dan Astenopia Santri Pondok Pesantren Ta’mirul Islam Surakarta - Faizza Respati Putri; Ahmad Ikliluddin; Yunani Setyandriana (Pusat Riset dan Inovasi Nasional, 2025)
Myopia is a refractive disorder that occurs when parallel rays from a distance are focused in front of the retina. This condition is not only experienced by older adults but also commonly affects children and adolescents during their growth period. Myopia can cause difficulty in seeing distant objects and has the potential to influence various aspects of life, such as academic achievement, visual comfort, and the development of other conditions like dry eyes and asthenopia. This study aims to analyze the relationship between myopic refractive status and academic performance, the incidence of dry eyes, and asthenopia among students in Islamic boarding schools. The research employed a quantitative approach with an observational analytic method and a cross-sectional design, involving 81 respondents. Data were analyzed using the chi-square test to determine the relationship between variables. The results revealed a statistically significant relationship (p < 0.001) between myopia and the three variables: academic performance, dry eye incidence, and asthenopia. These findings indicate that myopia may simultaneously affect students’ academic performance and ocular health. Therefore, regular eye examinations and early management are essential to prevent further negative impacts on learning activities and the overall quality of life of the students.